Temperature effect on rose downy mildew development under environmental controlled conditions (2014)
The rose downy mildew disease, caused by Peronospora sparsa Berkeley, is one of the most important that affect rose crops in Colombia. To manage this disease, flower growers must deal with high-costs due to the excessive application of fungicides, but without good results. Studies on P. sparsa behavior have shown its narrow relationship with environmental conditions. In this study, the temperature effect was evaluated during the infection and sporulation of P. sparsa in Charlotte leaflets, a susceptible commercial variety, through an environmental controlled conditions system. Infection and sporulation were observed at different temperatures in a range of from 4 to 40°C. Infection with the absence of or very low sporulation was observed at 4°C. The most favorable pathogen responses were between 15 and 18°C in terms of inoculum concentration and sporulation percentage. There was no infection or leaflet change above 35°C. According to the results, sporulation can occur from 4 to 33°C, confirming the fact that P. sparsa is able to reproduce throughout a wide temperature range.